Effect of nonsurgical periodontal therapy on thyroid stimulating hormone in hypothyroid patients with periodontal diseases - Ruchi Ramesh Bhankhar; Shital Hungund; Preeti Kambalyal; Vatsala Singh; Kushal Jain (Wolters Kluwer Medknow Publications, 2017)
Background: The endocrine and the immune system demonstrate a mutual relationship under pathophysiologic conditions. Thyroid hormone plays an important role in the regulation of normal growth and development. Although there is proven bidirectional influence of systemic diseases on periodontium, there are fewer studies on the effect of periodontal therapy on the hormone levels. This study aims to assess the effect of nonsurgical periodontal therapy (NSPT) on serum thyroid stimulating hormone (TSH) levels in hypothyroid patients with periodontal diseases. Materials and Methods: A total of 30 randomly chosen subjects of which 15 known hypothyroidism patients (13 females and 2 males) who were under medication for the same and 15 healthy individuals were enrolled into the study. Clinical parameters and serum TSH levels were recorded at baseline in both the groups, whereas TSH levels were recorded again at 3 months after NSPT in hypothyroid patients. Intergroup comparison was carried out by Tukey Kramer multiple comparisons test and the difference in variables was analyzed using one-way analysis of variance. Results: Mean values of TSH in hypothyroid patients 3.48 ± 1.41 μIU/ml showed significant reduction to 2.31 ± 1.24 μIU/ml (P ≤ 0.05) at 3 months follow up of NSPT. Clinical parameters improved significantly in both the groups after NSPT (P ≤ 0.05). Alveolar bone loss was greater in hypothyroid patients than the control group at baseline. Conclusion: NSPT plays a major role in improving periodontal conditions by reducing inflammatory markers and thereby influencing the thyroid hormone. Thus, immune system serves as an important link between thyroid dysfunction and periodontal diseases.